Agalsidase alfa: enzyme therapy for Anderson––Fabry disease. Issue 2 (1st November 2004) - Pastores, G M
Agalsidase alfa is a recombinant formulation of human αα-galactosidase A for use in the treatment of Anderson––Fabry disease, an X-linked lysosomal storage disorder. Its mechanism of action is the intracellular hydrolysis of an incompletely metabolized macromolecule; a glycosphingolipid which progressively accumulates in the human αα-galactosidase A-deficient tissues of untreated Anderson––Fabry disease patients. Its efficacy is primarily dependent on targeted delivery of sufficient enzyme to diverse cellular sites of pathology; through a routing pathway that is contingent on the requisite pattern of glycosylation and sialylation of the carbohydrate residues of the primary protein sequence. In clinical trials, supplementary studies and practice, the regular intravenous infusion of agalsidase alfa has been shown to modify the natural history of Anderson––Fabry disease; which in the untreated patient is characterized by acroparesthesias and gastrointestinal problems with onset in childhood and among affected adults by significant morbidity resulting from dysfunction of the renal, cardiac and cerebrovascular systems. Enzyme administrations have been well tolerated, even though a significant proportion of treated male patients seroconvert (i.e., develop antibodies directed against the enzyme). High antibody titers may provoke infusion-related reactions; problems that appear to be mitigated by the use of appropriate premedication(s) among symptomatic patients. Additionally, neutralizing antibodies may develop, however, loss of clinical efficacy has not been encountered (as yet) among these patients, perhaps because circulating antibody titers appear to decline with ongoing treatment. Disease progression has been noted in certain Anderson––Fabry disease patients on therapy, likely influenced by the extent of pre-existing and irreversible pathology. These observations highlight the need for appropriate timely intervention and a fuller understanding of the determinants of clinical response. Systematic investigations of the natural history of the disease and its management should enable development of guidelines for the stratification of patients (based on disease stage or risk of developing complications) to facilitate prognostication and selection of the optimal therapeutic regimen.